1996
DOI: 10.1079/bjn19960112
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation status as an index to evaluate the influence of dietary fats on vitamin E requirements of young pigs

Abstract: The aims of the present study were to establish a suitable criterion for estimating the vitamin E requirement for young pigs, and to investigate the influence of dietary fats on the requirement of this nutrient. In Expt 1 weaned pigs were given a semi-purified diet supplemented with 0,20, or 100 mg DLa-tocopheryl acetate/kg. Pigs in Expt 2 were fed on diets containing 10 g sunflower oil (SO) stripped of vitamin E/kg in diets 1 and 2,100 g SO/kg in diets 3 and 4, and 100 g tallowkg in diet 5. Diets 2,4 and 5 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
4
13
1
2
Order By: Relevance
“…In such a situation, increasing membrane vitamin E and improving its resistance to peroxidation, even if only moderately, might serve to decrease the extent of erythrocyte peroxidation occurring in vivo. This possible effect of vitamin E in vivo is supported by the observation that vitamin E-deficient pigs have higher circulating erythrocyte TBARS (57) and that vitamin E supplementation restored MDA to normal concentrations in erythrocytes of T1DM children (58).…”
Section: Discussionsupporting
confidence: 50%
“…In such a situation, increasing membrane vitamin E and improving its resistance to peroxidation, even if only moderately, might serve to decrease the extent of erythrocyte peroxidation occurring in vivo. This possible effect of vitamin E in vivo is supported by the observation that vitamin E-deficient pigs have higher circulating erythrocyte TBARS (57) and that vitamin E supplementation restored MDA to normal concentrations in erythrocytes of T1DM children (58).…”
Section: Discussionsupporting
confidence: 50%
“…: 20,27,8), Schweinen (z.B. : 22,32,11,9) und Geflügel (z.B. : 28, 30) hatten die Vitamin-E-Zulagen einen signifikanten Einfluß auf die Vitamin-E-Konzentration in den untersuchten Organ-und Gewebeproben (Tabellen 4 und 5).…”
Section: Diskussion Der Ergebnisseunclassified
“…The oxygen inflow during pressing and storage of pressed oil seeds may be one cause of fat oxidation and vitamin E degradation (Dove and Ewan, 1991;Halliwell and Chirico, 1993;Schone et al, 1995;Wang et al, 1996). Other authors found that oxidised lipids may reduce vitamin E absorption (Wang et al, 1996) and may increase the metabolic vitamin E requirements (Galvin et al, 1994;Sallmann and Fuhrmann, 1995) resulting in lower vitamin E concentrations in body samples (Sheehy et al, 1993;Baker, 1997;Baker and Davies, 1997). The mechanism responsible may be due to the role of a-tocopherol in modulating the free-radical induced peroxidation.…”
Section: Methodsmentioning
confidence: 99%